2011
DOI: 10.1007/s10311-011-0334-2
|View full text |Cite
|
Sign up to set email alerts
|

13C-dating, the first method to calculate the relative age of molecular substance homologues in soil

Abstract: International audienceThis article reports the design of 13C-dating, the first method to calculate the relative age of molecular substance homologues occurring in fractions from the same soil sample. Soil is a major carbon pool impacting modern climate by CO2 release and uptake. Molecular substances that sequester carbon in soils are poorly known due to the absence of methods to study molecular-level C dynamics over agricultural time scales, e.g. 0-200 years. Here I design a method to calculate the relative ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…These conflicting results highlight the challenges of field-based studies due to possible reworking and multiple sources of n-alkanes within soils (e.g. Lichtfouse, 2011). Upon heating and increasing maturity, n-alkane δ 13 C values appear to not be altered up to the pre-oil generation window.…”
Section: Plant Wax Alteration and Diagenetic Fatementioning
confidence: 99%
“…These conflicting results highlight the challenges of field-based studies due to possible reworking and multiple sources of n-alkanes within soils (e.g. Lichtfouse, 2011). Upon heating and increasing maturity, n-alkane δ 13 C values appear to not be altered up to the pre-oil generation window.…”
Section: Plant Wax Alteration and Diagenetic Fatementioning
confidence: 99%
“…In addition, analytical methods should be developed to identify and quantify bound residues (Loeffler et al 2020). For instance, molecular level 13 C-tracing has allowed to evidence the occurrence of temporal pools of the same organic compound in various fractions of the same soil sample (Lichtfouse et al 1998;Lichtfouse 1999Lichtfouse , 2012. Moreover, cleavage of sedimentary matter with Na 18 OH has shown that DDT metabolites are bound to organic macromolecules (Kalathoor et al 2015).…”
Section: Bound Residuesmentioning
confidence: 99%
“…In 2012, by using the first-order law set up previously to calculate the turnover of individual soil compounds (eq 2), 28 I determined the relative age of individual n-alkanes occurring in six temporal pools of the same soil sample (eq 3): free homologues from the bulk extract, bound homologues from humin extraction, bound homologues from humin pyrolysis, and free homologues in the three particle-size fractions. 4 Results showed relative ages ranging from −6.7 years for the oldest homologues in humin to +25.1 years for the youngest homologues in the 200−2000 μm particle size fraction, compared to the homologues in the bulk soil extract (Figure 3). I named the corresponding method " 13 C-dating", 4…”
Section: ■ Temporal Pools Of Individual Substancesmentioning
confidence: 99%
“…4 Results showed relative ages ranging from −6.7 years for the oldest homologues in humin to +25.1 years for the youngest homologues in the 200−2000 μm particle size fraction, compared to the homologues in the bulk soil extract (Figure 3). I named the corresponding method " 13 C-dating", 4…”
Section: ■ Temporal Pools Of Individual Substancesmentioning
confidence: 99%
See 1 more Smart Citation